1979
DOI: 10.1016/0035-9203(79)90121-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vivax malaria with sulfadoxine-pyrimethamine and with pyrimethamine alone

Abstract: The effect of pyrimethamine and the combination of pyrimethamine-sulfadoxine (Fansidar) upon the termination of the acute attack of vivax malaria was studied in Thailand. Pyrimethamine was found to be ineffective, providing clearance of parasitaemia in only two of six patients by the end of seven days following treatment. The combination, administered in a two-tablet single dose (sulfadoxine 1 gm, pyrimethamine 50 mg) eliminated parasitaemia in only six of ten patients within seven days. Three tablets (sulfado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 4 publications
0
17
1
Order By: Relevance
“…vivax parasites seemed intrinsically resistant to SP. 9,10 However, there is evidence indicating that SP resistance in P. vivax also results from drug selection pressure. Because mixed species infections with P. falciparum and P. vivax are common in many malarious regions, 11 extensive use of SP to treat patients with P. falciparum malaria may have inadvertently exposed P. vivax to these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…vivax parasites seemed intrinsically resistant to SP. 9,10 However, there is evidence indicating that SP resistance in P. vivax also results from drug selection pressure. Because mixed species infections with P. falciparum and P. vivax are common in many malarious regions, 11 extensive use of SP to treat patients with P. falciparum malaria may have inadvertently exposed P. vivax to these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Fansidar, a fixed combination of sulfadoxine and pyrimethamine (S/P), is most often the alternative chosen when chloroquine-resistant P. falciparum parasites render chloroquine ineffective (4). However, S/P has not been recommended for primary therapy of vivax malaria due to the poor clinical efficacy reported when the drug was introduced in the 1950s (13,14,26,49,64,68).In both P. falciparum and P. vivax, the dihydrofolate reductase (DHFR, E.C. 1.5.1.3) enzyme is the therapeutic target of the pyrimethamine component of S/P (12,18,23,26,27,43,44,60).…”
mentioning
confidence: 99%
“…Since the two species cannot be differentiated on clinical grounds, malaria infections, whether due to P. falciparum or P. vivax, are treated with S-P. Unfortunately, S-P is less effective in clearing fever and parasites in patients infected with P. vivax than in those infected with P. falciparum (9,11). Earlier studies had already shown that sulfa drugs are less active against P. vivax than against P. falciparum (16,18,20).…”
mentioning
confidence: 99%